2015
DOI: 10.5897/ajbr2015.0848
|View full text |Cite
|
Sign up to set email alerts
|

Diastatic enzymes malting process optimisation of African finger millet for biotechnological uses

Abstract: This study sought to understand the importance of variation of steeping and germination conditions (temperature, pH and salts) on the quality of African finger millet malt in terms of diastic power (amylase and β-amylase), endo-(1,3) (1,4)-β-D-glucanase, -glycan content and protein profile. The results show that the physiological responses of African finger millet malted seeds are correlated to pH (acidity and alkalinity) but inversely correlated to temperature stress. The effect of the stresses on the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Klang et al ( 50 , 51 ) also reported an increase in the moisture content of maize and rice grains with increasing soaking time. Many authors including Kolawole and Kolawole ( 70 ) have shown that the use of plant ash during soaking improves germination while reducing soaking time. Diffusion of these elements in the seed is influenced by the soaking time, the composition of the epidermis, and the soaking temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Klang et al ( 50 , 51 ) also reported an increase in the moisture content of maize and rice grains with increasing soaking time. Many authors including Kolawole and Kolawole ( 70 ) have shown that the use of plant ash during soaking improves germination while reducing soaking time. Diffusion of these elements in the seed is influenced by the soaking time, the composition of the epidermis, and the soaking temperature.…”
Section: Resultsmentioning
confidence: 99%